Corrosion inhibition of mild steel determined using blended bitter leaf (Vernonnia amygdalina) extract and honey in dilute H2SO4 and HCl acid solutions - Abba-Aji, M. A.; Muhammad, A. B.; Onwe, D. D. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The inhibitive effect of bitter leaf extract (Veronia amygdalina) and honey hybrid on the corrosion of mild steel in dilute H2SO4 and HCl solutions was investigated using weight loss method. Various concentrations of the leaf extract and honey (5 to 25ml), and immersion times (96 to 240hrs) were recorded at room temperature (32°C), which were used to calculate the corrosion rates and inhibition effects. Inhibition was found to increase with increase in the inhibitor concentration. The inhibitive effect of honey as inhibitor on the corrosion of mild steel in dilute hydrochloric acid (HCl) solution with 54% efficiency and dilute H2SO4 acid solution with 48.03% inhibition efficiency were not as effective as that of hybrid with 72.48% inhibition efficiency. The results obtained indicated that both bitter leaf extract and honey could serve as an effective inhibitor for the corrosion of mild steel in dilute H2SO4 acid and dilute HCl solution.